Novel approach to evaluate central autonomic regulation in attention deficit/hyperactivity disorder (ADHD) - Sekaninova, N; Mešťaník, Michal; Mešťaníková, Andrea; Hamráková, Andrea; Tonhajzerová, Ingrid (Physiological research, 2019)
Attention deficit/hyperactivity disorder (ADHD) is one of the most commonly diagnosed developmental disorders in childhood characterized by hyperactivity, impulsivity and inattention. ADHD manifests in the child's development by deficits in cognitive, executive and perceptor-motor functions, emotional regulation and social adaptation. Although the exact cause has not yet been known, the crucial role in the development of this disease plays the interaction of genetic, neurobiological and epigenetic factors. According to current knowledge, ADHD is defined as a biological dysfunction of central nervous system with genetically or organically defined deficits in noradrenergic and dopaminergic neurotransmission associated with structural abnormalities, especially in prefronto-striatal regions. In this context, a significant part of the difficulties could be due to a faulty control of fronto-striato-thalamo-cortical circuits important for attention, arousal and executive functions. Moreover, ADHD is associated with abnormal autonomic regulation. Specifically, reduced cardiac-linked parasympathetic activity associated with relative sympathetic dominance indexed by low heart rate variability can represent a noninvasive marker for prefrontal hypoactivity. However, the mechanisms underlying altered autonomic regulation in ADHD are still unknown. In this aspect, the evaluation of central autonomic regulation by noninvasive methods, namely pupillometry and eye-tracking, may provide novel information for better understanding of the neurobiological pathomechanisms leading to ADHD.
Keywords: hyperkinetická porucha; Attention; pohyby očí; Attention Deficit Disorder with Hyperactivity; lidé; autonomní nervový systém; Eye Movements; pozornost; Brain; Autonomic Nervous System; mozek; Humans